Stereospecific Synthesis and Biological Evaluation of Monodesmethyl Metabolites of (+)-13a-(S)-Deoxytylophorinine as Potential Antitumor Agents - Yu, Pengfei; Lv, Haining; Li, Chao; Ren, Jinhong; Ma, Shuanggang; Xu, Song; Chen, Xiaoguang; Yu, Shishan (Synthesis, 2012)
Three major monodesmethyl metabolites of (+)-13a-(S)-deoxytylophorinine were synthesized stereospecifically and their configurations at C-13a were determined. Biological assays revealed that one of the metabolites, 3-O-desmethyl-13a-(S)-deoxytylophorinine, had a higher cytotoxic potency than the parent compound or the positive controls doxorubicin (Adriamycin) and paclitaxel (Taxol).
Keywords: alkaloids; medicinal chemistry; antitumor agents; stereoselective synthesis